التراث العربي الإسلامي في شرق أفريقية: دراسة أولية لمخطوط: «تاريخ ولاية المزارعة في أفريقية الشرقية» تأليف الشيخ الأمين بن علي المزروعي - صغيرون, إبراهيم الزين (مجلة عالم الكتب, 1985)
A preliminary study of a MS in the possession of the heirs of ʿAlī Jaʿfar al-Wahṭ al-Saqqāf al-ʿAlawī al-Ḥaḍramī in Mekka: 99 large pages, two annexes to pp. 52 and 97, two typewritten commentaries with explanatory remarks by ʿAlī Jaʿfar al-Wahṭ al-Saqqāf, who also wrote an introduction to the MS. According to Ṣughayrūn, this must be the original MS. Another copy is in the possession of the Mazrūʿī family in Mombasa (see Ritchie 1995), and photographs of the mother-copy are in the Kenyan National Archives and in the Central Library of al-Malik ʿAbd al-ʿAzīz University (former Jāmiʿat Umm al-Qurà) in Mekka. The MS most probably was written during World War II; its author died in 1947 (or 1949). On pp. 192-193 the contents of the MS. Pp. 193-195 on al-Mazrūʿī and his work.
Keywords: Zanzibar

Riḥlat al-Sulṭān Khalīfa b. Ḥārib ilà Urūbā, 1937-1960 - Mughayyirī, Saʿīd b. ʿAlī (Ministry of National Heritage and Culture, 1985)
Keywords: Zanzibar

K. al-Salwa fī Akhbār Kilwa - Ṣulaybī, Muḥammad ʿAlī al- (Ministry of National Heritage and Culture, 1985)
Pp. 10-14: this edition is based on a MS in the British Museum (Or. 2666). In K. Zinjibār, which has been printed in Cairo, the copyist, ʿAbdl. b. Muṣabbiḥ al-Ṣawwāfī, is considered the author of the MS. The MS of ʿAbdl. b. Muṣabbiḥ al-Ṣawwāfī, which was completed 5 Jum. I 1294/1877, was copied recently by Muḥ. b. Ḥasan al-Ramaḍānī, completed 16 Febr. 1405/10 Nov. 1984. It comprises 10 chapters on 30 pp. It was composed by al-Ṣawwāfī on the request of Sultan Barghash b. Saʿīd of Zanzibar and it is not much more than a list of the rulers of Kilwa, with a long introduction on Bayān al-ʿAql wa-Ādābihi. It is said in the MS that its original composer was born in Shawwāl 904/1499.
Keywords: Zanzibar